Energy absorbing capability of materials subjected to impact under gravity loading - Shah, Qasim Hussain; Abid, Hasan M.; Rosli, Adib (IIUM Press, 2011)
Energy absorbers are systems that convert kinetic energy into other fom1s ofenergy, such as pressure energy in compressible fluids, elastic strain energy in solids, and plastic defonnation energy in defom1able solids. The process of conversion for plastic defonnation depends, among other factors, on the magnitude and method of application of loads, transmission rates, defonnation displacement pattems, and matelial properties. The applications of defonnable energy absorbers have been paid serious attention for several decades, for the means of safety. The aim is to minimize the impact by controlling the deceleration pulse during impact, i.e. extending the period of dissipation of kinetic energy. Cushioning devices on vehicle bumpers, crash retarders in emergency systems of lifts, and some crash barriers used as road blocks are everyday examples. The vital application of this work is reliability of energy to absorb massive landing force, for instance the missile safeguards when landing on the ground. This high energy absorption ability can be practically applied to rocket systems for sending the chips or any other important materials into space or far-distant places, thus protecting the chips from damage.